Porous organic polymer containing thianthrene ring as well as preparation method and application of porous organic polymer

The preparation of porous organic polymers containing thia anthracene rings by mechanical ball milling method solves the problem of converting elemental sulfur into sulfur-containing polymers, and improves the efficiency of photocatalytic CO2, achieving efficient and safe polymer preparation and photocatalytic application.

CN119823381AActive Publication Date: 2025-04-15LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311329907.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

现有技术难以通过简单、安全和高效的方法将单质硫转化为含硫的功能性聚合物,且光催化CO2还原的催化剂存在光吸收窄、电荷转移缓慢和催化活性位点有限的问题。

Method used

The halogen monomer, sulfur element and alkaline catalyst were mixed by mechanical ball milling to prepare a porous organic polymer containing thia anthracene ring, which was used as an efficient photocatalyst for CO2 reduction reaction.

Benefits of technology

It realizes efficient preparation of porous organic polymers containing thia anthracene under mild conditions, improves the efficiency of photocatalytic CO2 reaction, and has good dispersion and stability of the material, which is suitable for large-scale industrial preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823381A_ABST
    Figure CN119823381A_ABST
Patent Text Reader

Abstract

The invention discloses a porous organic polymer containing a thianthrene ring as well as a preparation method and application of the porous organic polymer. The porous organic polymer comprises a plurality of repetitive structural units, the repetitive structural units have a structure shown in the following formula: # imgabs0 #, and a dotted line represents a bond connection position. The preparation method of the porous organic polymer containing the thianthrene ring is simple in step, mild in condition and suitable for large-scale production, popularization and application, and meanwhile the prepared porous organic polymer containing the thianthrene ring has good performance of photocatalytic reduction of carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic compounds, and in particular relates to a porous organic polymer containing a thianthrene ring and a preparation method and application thereof. Background Art

[0002] Sulfur (S8) is one of the most produced by-products in the global petrochemical industry. It can slowly oxidize or burn in the air, causing serious safety problems and problems such as acid rain that harm the ecological environment. Therefore, the resource utilization of elemental sulfur has become a global problem. If elemental sulfur can be directly converted into sulfur-containing functional polymers by environmentally friendly methods, it will have important academic significance and industrial value. Elemental sulfur is mainly represented by the S8 ring, which can be converted into a linear chain through the formation of a diradical intermediate at a temperature of >432K. The homopolymerization of the S8 ring is an equilibrium process. At room temperature, the long polysulfide chain tends to depolymerize, which also limits the sulfur content in the polymer to a certain extent. In addition, sulfur can cross-link polymer chains and can copolymerize with many compounds, which makes it possible to be incorporated into some stable polymer products at room temperature. At present, the conversion of elemental sulfur into sulfur-containing functional polymers has aroused the research interest of scientists. The introduction of sulfur into the conjugated polymer structure is conducive to the electron transport in the structure and the construction of high-performance polymers. Although great progress has been made in the development of elemental sulfur, it is still difficult to directly convert sulfur powder into components in polymers, mainly due to the poor solubility of sulfur in organic solvents and its certain toxicity to transition metal catalysts or free radical initiators, which greatly restricts their application in polymer synthesis.

[0003] Sulfur-containing polymers are a series of relatively complex high molecular polymers with some special excellent properties. The introduction of sulfur atoms can regulate the thermal stability, mechanical properties, electrical and optical properties of polymers. This makes them widely used in optical, optoelectronic and photochemical materials, as well as pharmaceutical preparations based on biopolymers, proton conductive electrolytes, lithium-sulfur battery cathodes and electromembrane processes. Timothy M. Swager's group [Nat. Chem., 2018, 10, 1023-1030.] pioneered a new nucleophilic aromatic substitution method, using thiol-containing monomers as sulfur sources to prepare porous organic polymers containing sulfur rings. The obtained product has a specific surface area of ​​up to 813 m 2 g -1. However, this new method involves the use of dithiol compounds, anhydrous solvents and a long condensation process, which is not suitable for scale-up experiments. Due to the disadvantages of thiols such as unpleasant odor, unstable properties and commercial unavailability, the use of thiols as starting materials for synthesis is not ideal. Compared with other sulfur-containing reagents, sulfur powder is abundant, non-toxic, non-volatile, stable and odorless. Recent studies have shown that elemental sulfur can participate in free radical transformations and introduce sulfur atoms into the molecular skeleton under mild conditions, making it an ideal source of sulfur atoms in organic molecules. A prerequisite for introducing sulfur into polymers is to open the S8 of the eight-membered ring. The opening of the S8 ring may involve free radical or ionic mechanisms. The latter mechanism can activate S8 through nucleophilic or electrophilic catalytic mechanisms. At present, the methods for preparing sulfur-containing polymers using elemental sulfur are extremely limited, and only a few studies have been reported. Usually, sulfurized polymers are obtained by bulk polymerization at high temperatures (≥159°C). There are many problems associated with this polymerization process, including but not limited to: inhomogeneity of the synthesized polymer due to poor miscibility of the monomers or different reactivity of the monomers at high temperatures, completely uncontrollable self-acceleration, release of toxic gas H2S due to side reactions, and the limitation of only being able to select high-boiling-point comonomers due to high reaction temperatures. Therefore, whether from the perspective of synthesis process or synthesis operation, it is difficult to achieve large-scale industrial preparation and application of vulcanized polymers at this stage. If you want to apply and prepare this sulfur-containing polymer material in industry, first of all, a simpler and safer method for synthesizing this type of polymer needs to be explored.

[0004] The key to the CO2 reduction reaction lies in the adsorption and activation of CO2. Traditional CO2 reduction requires a high temperature and high pressure environment to activate CO2 molecules. If light energy is introduced into this reaction system, it is possible to achieve this reaction at room temperature and pressure. Photocatalytic CO2 reduction is a new technology that uses the response of semiconductor photocatalysts to light to convert light energy into chemical energy by converting CO2 into C1 compounds. Because of its energy saving and green environmental protection, it has become an important scientific and technological issue in the field of photocatalysis. The core issue of photocatalytic CO2 reduction is the design, development and research of suitable photocatalysts. The development of new and efficient photocatalytic materials is the key to realizing photocatalytic CO2 reduction using solar energy, and it is also the inevitable trend and development direction for the further practicalization of photocatalysis. Since hexaazatrinaphthalene has a conjugated structure, it can be used as a luminescent material. The currently synthesized hexaazatrinaphthalene compounds are mainly organic porous materials, but hexaazatrinaphthalene-type porous polymers containing thianthrene rings have not been reported. Therefore, it is urgent to develop a porous polymer containing thianthrene rings and use it as an efficient photocatalyst.

[0005] The essence of photocatalytic CO2 reduction (CO2 reduction reaction, CO2RR) is a redox process induced by light, which mainly includes two processes: (1) adsorption of CO2 molecules by the reaction sites of photocatalytic materials; (2) redox process between adsorbed CO2 and photogenerated electrons and holes. Therefore, improving the light absorption efficiency of photocatalytic materials, enhancing their adsorption and activation ability for CO2, and improving the separation efficiency of photogenerated electrons and holes are key factors in constructing efficient photoreduction catalysts. However, the catalysts currently developed are limited by factors such as narrow light absorption, slow charge transfer and limited catalytic active sites, resulting in serious photogenerated charge recombination problems, which in turn significantly limits their photocatalytic efficiency. Therefore, developing efficient, cheap and highly stable photocatalysts is a major challenge faced in improving the efficiency of photocatalytic CO2 reduction.

[0006] In recent years, regular and ordered crystalline covalent organic frameworks (COFs) have been regarded as a new type of organic semiconductor polymer materials due to their π-conjugated characteristics of the skeleton and the characteristics of easy regulation and functionalization of the pore structure, showing great application potential in the process of artificial synthetic photocatalysis. Among them, crystalline covalent triazine frameworks (CTFs) composed of triazine groups with excellent light absorption ability have attracted extensive research attention. Their excellent organic semiconductor properties have made them widely used in various photocatalytic processes, such as water decomposition to produce hydrogen and multiphase organic reactions. Some triazine organic polymer materials reported in the hydrolysis reaction showed photocatalytic activity comparable to or even better than that of inorganic semiconductors. However, due to the mismatch of energy band positions and the inability to meet high overpotentials, the application of triazine polymers in photocatalytic CO2 conversion is still relatively small. CTFs use covalent chemical bonds to link triazines and other organic structural units at the molecular scale to form periodic and ordered framework materials. For example, crystalline CTFs can be prepared by high-temperature (low-temperature) self-condensation reaction of aromatic cyano groups under the catalysis of Lewis acid (Brown acid). In addition, the condensation reaction between aromatic aldehydes / amines and diformamidine also provides an important way to create crystalline CTFs. However, it should be pointed out that there is an obvious shortcoming in the above preparation methods, that is, it is difficult to simply functionalize the skeleton structure of the prepared CTFs. It is usually necessary to design the organic building blocks of CTFs in a specific molecular structure to achieve secondary modification of CTFs or regulation of the pore structure. However, the multi-step and complex preparation process is often not conducive to further promoting its application in artificial synthetic photocatalytic processes. Therefore, it is an urgent problem to provide a simple method for preparing functionalized triazine polymers and use them for the reduction of carbon dioxide. Summary of the invention

[0007] The main purpose of the present invention is to provide a methylated covalent triazine polymer and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0009] An embodiment of the present invention provides a porous organic polymer containing a thianthrene ring, wherein the porous organic polymer includes a plurality of repeating structural units, and the repeating structural units have structures shown in formulas (I) to (III):

[0010]

[0011] The dashed lines represent the bond connection locations.

[0012] The embodiment of the present invention further provides a method for preparing a porous organic polymer containing a thianthrene ring, which comprises:

[0013] At least a mechanical ball milling method is used to ball mill a mixture containing a halogenated monomer, a sulfur element and an alkaline catalyst to obtain a porous organic polymer containing a thianthrene ring.

[0014] The embodiment of the present invention also provides a porous organic polymer containing thianthrene rings prepared by the aforementioned preparation method.

[0015] The embodiment of the present invention also provides the use of the aforementioned porous organic polymer containing thianthrene rings in photocatalytic reduction of carbon dioxide.

[0016] The embodiment of the present invention further provides a photocatalytic material, which at least includes the aforementioned porous organic polymer containing thianthrene rings, and the photocatalytic material is at least used in a reaction of reducing carbon dioxide.

[0017] The embodiment of the present invention also provides a method for photocatalytic reduction of carbon dioxide, which comprises:

[0018] The catalyst is placed in a gas-solid photocatalytic reaction system containing water and carbon dioxide, and then subjected to a photocatalytic reaction, thereby reducing carbon dioxide to carbon monoxide;

[0019] Wherein, the photocatalyst includes the aforementioned porous organic polymer or photocatalytic material containing thianthrene rings.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention regulates the DA structural unit in the polymer through a halogen doping strategy, and the structural difference is small through fine-tuning by halogen atom substitution, and the degree of comparison is high. At the same time, the optical band gap and LUMO energy level of the polymer can be regulated to achieve the purpose of regulating the photocatalytic activity; at the same time, the porous organic polymer containing thianthrene ring prepared by the present invention has good dispersibility and stability;

[0022] (2) The present invention adopts a simple, efficient and mild ball milling synthesis method to effectively avoid the defect of a small amount of metal residue in the polymer pores due to the high temperature of the traditional heating reaction;

[0023] (3) The present invention further improves the photocatalytic activity of the polymer by introducing N and S atoms that can serve as active sites for redox reactions at the photocatalytic interface into the polymer structure design. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 is the H NMR spectrum of the model monomer anthracenethioide in Example 1 of the present invention;

[0026] Figure 2 is the NMR carbon spectrum of the model monomer anthracenethioide in Example 1 of the present invention;

[0027] Figure 3 is the mass spectrum of the model monomer anthracenethioide in Example 1 of the present invention;

[0028] Figure 4a-4b is a nitrogen adsorption isotherm and pore size distribution curve of BM-S-HATN-Cl prepared in Example 2 of the present invention;

[0029] Figure 5 is a Fourier transform infrared (FT-IR) image of BM-S-HATN-Cl prepared in Example 2 of the present invention;

[0030] Figure 6 The solid state NMR carbon spectrum (ss 13 C NMR) spectra;

[0031] Figure 7a-Figure 7b is a catalytic performance diagram of BM-S-HATN-F and BM-S-HATN-Cl in Example 3 of the present invention;

[0032] Figure 8 This is a schematic diagram of the photocatalytic cycle of BM-S-HATN-Cl in Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution mainly utilizes sulfur powder, halide monomers, solid base catalysts and ball milling to prepare porous organic polymers containing thianthrene rings. The synthesis steps are simple and the conditions are mild. It is suitable for large-scale production promotion and application, and has good practical prospects for photocatalytic reduction of carbon dioxide.

[0034] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Specifically, as one aspect of the technical solution of the present invention, a porous organic polymer containing a thianthrene ring includes a plurality of repeating structural units, and the repeating structural units have structures shown in formulas (I) to (III):

[0036]

[0037] The dashed lines represent the bond connection locations.

[0038] Furthermore, the specific surface area of ​​the porous organic polymer containing thianthrene rings is 120 to 950 m 2 / g, pore size is 1~100nm.

[0039] Furthermore, the repeating structural unit has a structure as shown in formula (II):

[0040]

[0041] The dashed lines represent the bond connection locations.

[0042] Another aspect of the embodiments of the present invention further provides a method for preparing a porous organic polymer containing a thianthrene ring, comprising:

[0043] At least a mechanical ball milling method is used to ball mill a mixture containing a halogenated monomer, a sulfur element and an alkaline catalyst to obtain a porous organic polymer containing a thianthrene ring.

[0044] In some preferred embodiments, the halide monomer is selected from any one or more combinations of compounds having the following structural formulas:

[0045]

[0046] Wherein, X is a halogen atom, and R is selected from any one of -CHO, -OH, -CN, and -COOH.

[0047] Furthermore, the halide monomer is selected from compounds having the following structural formula:

[0048]

[0049] Wherein, X is a halogen atom.

[0050] In some preferred embodiments, the halogenated monomer includes any one or more combinations of octafluoronaphthalene, tris(pentafluorophenyl)phosphine, 2,3,5,6-tetrafluorohydroquinone, 2,3,5,6-tetrafluoroterephthalaldehyde, 2,3,5,6-tetrafluorothiophenol, 2,3,5,6-tetrafluoroterephthalonitrile, 2,3,5,6-tetrachloroterephthalonitrile, 1,2,7,8,13,14-hexachloro-substituted hexaazanaphthalene, 1,2,7,8,13,14-hexafluoro-substituted hexaazanaphthalene, 1,2,7,8,13,14-hexabromo-substituted hexaazanaphthalene, and 2,3,6,7,10,11-hexabromotriphenylene.

[0051] In some preferred embodiments, the halide monomer includes halogenated hexaazatrinaphthalene, but is not limited thereto.

[0052] In some preferred embodiments, the elemental sulfur includes S8, but is not limited thereto.

[0053] In some preferred embodiments, the alkaline catalyst includes any one or more combinations of sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium tert-butoxide, sodium methoxide, sodium ethoxide, sodium carbonate, potassium carbonate, and cesium carbonate, and is not limited thereto.

[0054] In some preferred embodiments, the preparation method specifically includes: mixing a halide monomer, a sulfur element and an alkaline catalyst, and then ball-milling the obtained mixture in a protective atmosphere by mechanical ball milling to obtain the porous organic polymer containing the thianthrene ring; wherein the ball milling frequency is 10-30HZ, the ball milling time is 0.5-20h, and the ball-to-material ratio is 5-40:1.

[0055] In some preferred embodiments, the ball mill used in the ball milling treatment includes a refrigerated mixing ball mill and a planetary ball mill.

[0056] In some preferred embodiments, in order to prevent the temperature in the tank from being too high during the ball milling process, a 10-minute rest period is performed after every 30 minutes of milling to obtain the corresponding organic porous polymer.

[0057] In some preferred embodiments, the mass ratio of the halide monomer, sulfur element and alkaline catalyst is 1:0.5-10:4-20.

[0058] In some preferred embodiments, the preparation method further comprises: after the ball milling treatment is completed, performing a de-alkali treatment on the obtained product.

[0059] In the present invention, a green and simple mechanical ball milling method is used to synthesize a new organic conjugated polymer (BM-S-HATN-X) connected by thianthrene rings with a π-π stacking structure from a nitrogen-rich precursor halogenated hexaazatrinaphthyl HATN-(X)6 (X is a halogen) and a sulfur element, and the elemental sulfur is directly and successfully and quickly converted into an organic porous polymer with redox activity in a solid phase reaction. Mechanochemical synthesis is derived from mechanical energy and is an environmentally friendly method with the advantages of short reaction time, uniform reaction phase, and high atom economy. Compared with the traditional heating thermal synthesis route for preparing sulfur-containing polymers, the mechanochemical polymerization method does not require heating, has fast reaction, no solvent, few side reactions, no self-acceleration, a wider range of monomer selection, and a more homogeneous reaction (regardless of the miscibility of sulfur with the monomer). By studying in detail the effects of ball milling materials, ball milling time, catalyst type and dosage, halogen atom type of monomer and grinding type on polymer yield and material porosity, a porous thianthrene-based two-dimensional covalent organic porous polymer material with π-electron conjugated nitrogen heteroaromatic rings is successfully prepared. The hexaazanaphthalene and thianthrene ring structural units contained in the material can improve the charge carrier mobility in the polymer network. For sulfur-containing heterocycles, the empty d orbital of sulfur may interact with guest ions for charge storage, and the low electronegativity of sulfur also provides lone pairs of electrons for the CS bonds of the heterocycle. This type of polymer has good light-harvesting ability and a suitable band gap, strong DA interaction and other advantages, which can improve the efficiency of the photocatalytic carbon dioxide reaction.

[0060] In some more specific embodiments, the method for preparing the porous organic polymer containing thianthrene rings comprises:

[0061] (1) A halogenated monomer, sulfur powder and an alkaline catalyst are mixed in a certain proportion, and then ground by mechanical ball milling to obtain a corresponding donor-acceptor porous polymer, i.e., a porous organic polymer containing a thianthrene ring, wherein the certain proportion refers to a mass ratio of the halogenated monomer, the sulfur powder and the alkaline catalyst of 1:0.5-10:4-20, and in the mechanical ball milling method, the ball-to-material ratio is 5-40:1, and the method is carried out under nitrogen or argon protection, the ball milling frequency is 10-30 Hz, and the ball milling time is 0.5-20 h.

[0062] (2) The mixed powder obtained in step (1) is taken out, and 0.5-3M hydrochloric acid is added thereto and stirred for 1-6 hours to remove excess alkali.

[0063] In some more specific embodiments, the method for preparing the porous organic polymer containing thianthrene rings comprises:

[0064] 1) sulfur powder, halogenated hexaazatrinaphthalene HATN-(X)6 (X=F, Cl or Br) and an alkali catalyst are weighed in a ball mill according to a certain stoichiometric ratio;

[0065] 2) After the mixture is mixed in a tank, ball milling is started. After the reaction is completed, the base is synthesized with dilute acid, and then washed and purified with water, DMF, and ethanol respectively. The residual sulfur powder in the reaction product is then removed by heating with DMF under nitrogen protection conditions. The product is collected, vacuumed and heated to dry, namely, a halogen-doped porous organic polymer photocatalyst containing thianthrene rings, i.e., a porous organic polymer containing thianthrene rings.

[0066] Furthermore, the ball mill described in step 1) is made of one of tungsten oxide, zirconium oxide, agate, stainless steel and the like.

[0067] Furthermore, the volume of the ball mill jar in step 1) is 10 mL-200 mL, and the number of ball mill beads is 1-10.

[0068] Furthermore, the alkaline catalyst in step 1) is one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium tert-butoxide, sodium methoxide, sodium ethoxide, sodium carbonate, potassium carbonate, and cesium carbonate.

[0069] Furthermore, the ball milling frequency in step 2) is maintained in the range of 10-30 Hz.

[0070] Furthermore, the ball milling reaction time in step 2) is 1h-20h.

[0071] Furthermore, the type of the dilute acid in step 2) is one or more of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and acetic acid.

[0072] Furthermore, the concentration of the dilute acid in step 2) is 0.5M-2M.

[0073] Furthermore, the DMF heating temperature in step 2) is between 50-150° C. The time for heating the washed sulfur powder is 10-72 hours.

[0074] Furthermore, the specific surface area of ​​the material prepared in step 2) is 120 to 950 m 2 / g, and the pore sizes are 1 to 100 nm respectively.

[0075] Another aspect of the embodiments of the present invention further provides a porous organic polymer containing a thianthrene ring prepared by the aforementioned preparation method.

[0076] Furthermore, the specific surface area of ​​the porous organic polymer containing thianthrene rings is 120 to 950 m 2 / g, pore size is 1~100nm.

[0077] Another aspect of the embodiments of the present invention further provides use of the aforementioned porous organic polymer containing thianthrene rings in photocatalytic reduction of carbon dioxide.

[0078] In the present invention, under the conditions of light illumination, carbon dioxide saturation, and the absence of photosensitizer and sacrificial agent, a porous organic polymer containing thianthrene ring is used as a catalyst for photocatalytic carbon dioxide reduction.

[0079] Another aspect of the embodiments of the present invention further provides a photocatalytic material, which at least includes the aforementioned porous organic polymer containing thianthrene rings, and the photocatalytic material is at least used in a reaction of reducing carbon dioxide.

[0080] Another aspect of the embodiments of the present invention further provides a method for photocatalytic reduction of carbon dioxide, comprising:

[0081] The catalyst is placed in a gas-solid photocatalytic reaction system containing water and carbon dioxide, and then subjected to a photocatalytic reaction, thereby reducing carbon dioxide to carbon monoxide;

[0082] Wherein, the photocatalyst includes the aforementioned porous organic polymer or photocatalytic material containing thianthrene rings.

[0083] Furthermore, the illumination adopts visible light λ>420nm.

[0084] Furthermore, the conditions adopted for the catalytic reaction include: the xenon lamp illumination range is 420nm to 780nm; the required carbon dioxide mass percentage is 5% to 99.99%; the required catalyst dosage is 1 to 10 mg; the water mass percentage in the solvent is 0% to 100%.

[0085] Furthermore, the reaction temperature of the photocatalytic carbon dioxide reduction experiment is 25°C.

[0086] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0087] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0088] Example 1

[0089] In a glove box filled with argon, anhydrous o-dichlorobenzene (0.5 ml), solid base catalyst cesium carbonate (978 mg) and sulfur powder (0.48 g) were mixed evenly and placed in a 10 ml agate ball mill, the ball mill was tightened, and the jar was placed on a ball mill, and reacted at 10-30 Hz for 0.5-5 hours. The product was taken out and washed with deionized water to remove the incompletely reacted inorganic salts, then extracted with water and dichloromethane, and the organic phase was concentrated. The organic phase was purified by silica gel column, and n-hexane was used as eluent to obtain a white crystalline product with a yield of 47-71%.

[0090] To characterize this model compound, refer to Figure 1 , Figure 2 and Figure 3 . 1 H NMR (400MHz, DMSO-d6, ppm): δ7.60 (4H, dd), δ7.37 (4H, dd); 13 C NMR (151MHz, DMSO-d6, ppm): δ134.90, 129.26, 128.75.MS (EI): calc.for C 12 H8S2: 216.0065; found: 216.0065

[0091] Example 2

[0092] 1.46 g HATN-Cl6, 1.94 g alkaline catalyst cesium carbonate and 1 g sulfur powder were mixed separately, and then put into a 200 mL ball mill together with ball milling balls, and ball milled at room temperature for 4 hours under nitrogen protection. After the reaction was completed, the ball mill was cooled to room temperature, the jar was opened, the solid powder was taken out, and it was rinsed with 1% hydrochloric acid several times to remove unreacted inorganic salts, and the excess sulfur powder was washed with carbon disulfide, and then refluxed in N, N-dimethylformamide solution for 24 hours to remove oligomers. Finally, the product was filtered and rinsed with methanol and ethanol respectively to obtain a dark brown product. The product was dried in a vacuum oven at 100°C overnight to obtain 1.25 g of a solid product, a porous organic polymer containing thianthrene rings, BM-S-HATN-Cl.

[0093] The nitrogen adsorption isotherm and pore size distribution curve of BM-S-HATN-Cl prepared in this example are shown in Figure 4a-4b As shown, the results show that its BET specific surface area is 574m 2 g-1, the pore size distribution is concentrated at 1.5nm and 2.6nm.

[0094] The Fourier transform infrared (FT-IR) image of BM-S-HATN-Cl prepared in this example is as follows: Figure 5 As shown in the infrared image of the polymer, the 1620 cm -1The peak at 1090cm is the unique stretching vibration peak in the HATN ring, proving the integrity of the HATN structure. -1 The weak peak at is the unique vibration peak of the CS bond in the anthrathiol ring.

[0095] The solid state NMR spectrum (ss 13 C NMR) Figure 6 As shown, the results indicate that the peak at 145 ppm corresponds to the carbon atoms in the HATN ring, and the peak at 133 ppm corresponds to the presence of the C-S bond in the anthrathiol ring.

[0096] Example 3

[0097] 1.5 g HATN-F6, 1.2 g alkaline catalyst cesium carbonate and 1 g sulfur powder were mixed separately, and then put into a 200 mL ball mill together with ball milling balls, and ball milled at room temperature for 4 hours under nitrogen protection. After the reaction was completed, the ball mill was cooled to room temperature, the jar was opened, the solid powder was taken out, and it was rinsed with 1% hydrochloric acid several times to remove unreacted inorganic salts, and the excess sulfur powder was washed with carbon disulfide, and then refluxed in N, N-dimethylformamide solution for 24 hours to remove oligomers. Finally, the product was filtered and rinsed with methanol and ethanol respectively to obtain a dark brown product. The product was dried in a vacuum oven at 100°C overnight to obtain 1.42 g of a solid product, a porous organic polymer containing thianthrene rings, BM-S-HATN-F.

[0098] In order to verify the beneficial effects of the present invention, the following tests were performed:

[0099] In order to investigate the photocatalytic carbon dioxide reduction effect of this series of organic porous polymers, their photocatalytic carbon dioxide reduction performance was tested according to the following method.

[0100] The test process is as follows: 5 mg of BM-S-HATN-F prepared in Example 3 and 5 mg of BM-S-HATN-Cl prepared in Example 2 were dispersed in 10 mL of ultrapure water, filtered, loaded onto a nylon filter membrane, and vacuum dried to remove water. The nylon filter membrane with the catalyst was placed in a gas-solid photocatalytic reaction system of water and carbon dioxide, and illuminated with a xenon lamp (λ>420 nm) for 4 hours. Figure 7a-Figure 7b As shown, the gas phase and liquid phase products were detected by GC7900 chromatograph and Bruker AC 400FT spectrometer (400MHz). The detection results show that the photocatalytic CO2 conversion rates of the BM-S-HATN-F and BM-S-HATN-Cl catalysts prepared in this embodiment to carbon monoxide are 607μmol / g / h and 445μmol / g / h, respectively.

[0101] The present invention regulates the DA interaction force of the material by doping different halogens (F, Cl or Br) into a porous organic polymer containing a thianthrene ring, so that BM-S-HATN-X not only has a controllable light capture ability, but also modulates the exciton dissociation energy and improves the photocatalytic efficiency, which greatly improves its efficiency in photocatalytic reduction of carbon dioxide.

[0102] The BM-S-HATN-Cl material prepared in Example 2 was subjected to a photocatalytic cycle experiment (catalytic reduction of carbon dioxide), and the results are as follows: Figure 8 As shown, it indicates that the prepared porous organic polymer containing thianthrene ring has good stability.

[0103] The BM-S-HATN-F prepared in Example 3 and the BM-S-HATN-Cl prepared in Example 2 were ultrasonically dispersed in water to obtain a uniformly dispersed solution, indicating that the prepared porous organic polymer containing thianthrene rings has good dispersibility.

[0104] Example 4

[0105] 500 mg of 2,3,6,7,10,11-hexabromotriphenylene (HBTPE), 800 mg of alkaline catalyst sodium ethoxide and 300 mg of sulfur powder were mixed respectively, and then put into a 50 mL ball mill together with ball milling balls, and ball milled at room temperature for 3-10 hours under nitrogen protection. After the reaction was completed, the ball mill was cooled to room temperature, the tank was opened, and the solid powder was taken out. It was rinsed with 1% hydrochloric acid several times to remove the unreacted alkaline catalyst, and the excess sulfur powder was washed with carbon disulfide, and then refluxed in N, N-dimethylformamide solution for 24 hours to remove oligomers. Finally, the product was filtered and rinsed with methanol and ethanol respectively to obtain a yellow-brown product. The product was dried in a vacuum oven at 120° C. overnight to obtain 432 mg of a solid product, a porous organic polymer BM-S-HBTPE containing thianthrene rings.

[0106] Example 5

[0107] 200 mg of 2,3,5,6-tetrafluoroterephthalonitrile (TFTPA), 400 mg of alkaline catalyst potassium tert-butoxide and 100 mg of sulfur powder were mixed respectively, and put into a 30 mL ball mill together with ball milling balls, and ball milled at room temperature for 4-8 hours under nitrogen protection. After the reaction was completed, the ball mill was cooled to room temperature, the tank was opened, and the solid powder was taken out. It was rinsed with 1% hydrochloric acid several times to remove the unreacted alkaline catalyst, and the excess sulfur powder was washed with carbon disulfide. Then, it was refluxed in N,N-dimethylformamide solution for 24 hours to remove oligomers. Finally, the product was filtered and rinsed with methanol and ethanol respectively to obtain a yellow product. The product was dried in a vacuum oven at 100°C overnight to obtain 216 mg of a solid product, a porous organic polymer containing thianthrene rings, BM-S-TFTPA.

[0108] The BM-S-HBTPE and BM-S-TFTPA prepared in Examples 4-5 were used for photocatalytic reduction of carbon dioxide using the same method as in Example 3, and a relatively good reduction effect was achieved. However, the ability to reduce carbon dioxide was not as good as that of the BM-S-HATN-Cl and BM-S-HATN-F materials prepared in Examples 2-3.

[0109] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0110] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A porous organic polymer containing thianthrene rings, characterized in that: The porous organic polymer comprises a plurality of repeating structural units, wherein the repeating structural units have structures as shown in formula (I)-(III): Among them, the dashed lines represent the bond connection locations; Preferably, the porous organic polymer containing thianthrene rings has a specific surface area of ​​120 to 950 m2 / g and a pore size of 1 to 100 nm; Preferably, the repeating structural unit has a structure as shown in formula (II).

2. A method for preparing a porous organic polymer containing thianthrene rings, characterized in that: include: At least a mechanical ball milling method is used to ball mill a mixture containing a halogenated monomer, a sulfur element and an alkaline catalyst to obtain a porous organic polymer containing a thianthrene ring.

3. The preparation method according to claim 2, characterized in that: The halogenated monomer is selected from any one or more combinations of compounds having the following structural formula: Wherein, X is a halogen atom, and R is selected from any one of -CHO, -OH, -CN, and -COOH; And / or, the halogenated monomer includes any one or more combinations of octafluoronaphthalene, tris(pentafluorophenyl)phosphine, 2,3,5,6-tetrafluorohydroquinone, 2,3,5,6-tetrafluoroterephthalaldehyde, 2,3,5,6-tetrafluorothiophenol, 2,3,5,6-tetrafluoroterephthalonitrile, 2,3,5,6-tetrachloroterephthalonitrile, 1,2,7,8,13,14-hexachloro-substituted hexaazanaphthalene, 1,2,7,8,13,14-hexafluoro-substituted hexaazanaphthalene, 1,2,7,8,13,14-hexabromo-substituted hexaazanaphthalene, and 2,3,6,7,10,11-hexabromotriphenylene; And / or, the halogenated monomer comprises halogenated hexaazatrinaphthalene; And / or, the elemental sulfur includes S8; And / or, the alkaline catalyst includes any one or more combinations of sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium tert-butoxide, sodium methoxide, sodium ethoxide, sodium carbonate, potassium carbonate, and cesium carbonate.

4. The preparation method according to claim 2, characterized in that: Specifically include: The halogenated monomer, sulfur element and alkaline catalyst are mixed, and then the obtained mixture is ball-milled by mechanical ball milling in a protective atmosphere to obtain the porous organic polymer containing thianthrene ring; wherein the ball milling frequency is 10-30HZ, the ball milling time is 0.5-20h, and the ball-to-material ratio is 5-40:

1.

5. The preparation method according to claim 2 or 4, characterized in that: The mass ratio of the halogenated monomer, the sulfur element and the alkaline catalyst is 1:0.5-10:4-20.

6. The preparation method according to claim 2 or 4, characterized in that: Also includes: After the ball milling treatment is completed, the obtained product is subjected to a de-alkali treatment.

7. A porous organic polymer containing thianthrene rings prepared by the preparation method according to any one of claims 2 to 6; preferably, the porous organic polymer containing thianthrene rings has a specific surface area of ​​120 to 950 m 2 / g, pore size is 1~100nm.

8. Use of the porous organic polymer containing thianthrene rings according to claim 1 or 7 in photocatalytic reduction of carbon dioxide.

9. A photocatalytic material, characterized in that: The photocatalytic material comprises at least the porous organic polymer containing thianthrene rings according to claim 1 or 7, and is used at least in a reaction of reducing carbon dioxide.

10. A method for photocatalytic reduction of carbon dioxide, characterized in that: include: The catalyst is placed in a gas-solid photocatalytic reaction system containing water and carbon dioxide, and then subjected to a photocatalytic reaction, thereby reducing carbon dioxide to carbon monoxide; Wherein, the photocatalyst comprises the porous organic polymer containing thianthrene rings as described in claim 1 or 7 or the photocatalytic material as described in claim 9.

Citation Information

Patent Citations

  • Method for adsorbing heavy metals in drinking water by using organic nanoporous polymer

    CN107824168A

  • A preparation method of thianthrene composite thermoelectric material

    CN109065699A

  • Two-dimensional covalent organic framework material containing crown ether group as well as preparation method and application of two-dimensional covalent organic framework material

    CN118221895A

  • Flame-Resistant High Energy Density Lithium-Ion Batteries and Manufacturing Method

    US20230101561A1

  • Lithium rechargeable electrochemical cell

    WO2007116363A2